Long-Term Vascular, Motor, and Sensory Donor Site Outcomes after Ulnar Forearm Flap Harvest - Brown, Emile N.; Chaudhry, Arif; Mithani, Suhail K.; Bluebond-Langner, Rachel O.; Feiner, Jeffrey M.; Shaffer, Cynthia K.; Call, Diana; Rodriguez, Eduardo D. (Journal of Reconstructive Microsurgery, 2014)
Use of the ulnar forearm flap (UFF) is limited by concerns for ulnar nerve injury and impaired perfusion in the donor extremity. Twenty UFFs were performed over a 6-year period. All patients underwent postoperative bilateral upper extremity arterial duplex studies. A subset of postoperative patients (n = 10) also had bilateral upper extremity sensory and motor evaluations, and functional evaluation via the Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH). Motor function was tested by digital and key grip dynamometry. Ulnar nerve sensation was tested by evaluation of one- and two-point perceived pressure thresholds and two-point discrimination using the Pressure-Specified Sensory Device (Sensory Management Services, LLC, Baltimore, MD). All UFFs were viable postoperatively. Mean follow-up was 28.8 months for vascular studies and 45.3 months for motor, sensory, and QuickDASH evaluations. Although mid and distal radial artery flow velocities were significantly higher in donor versus control extremities evaluated at less than 1 year postoperatively, there was no significant difference in extremities evaluated at later time points. Digital pressures, grip strength, key pinch strength, and ulnar sensation were equivalent between donor and control extremities. The mean QuickDASH score was 17.4 ± 23.8. The UFF can be harvested reliably and long-term follow-up shows no evidence of impaired vascular, motor, or sensory function in the donor extremity.
Keywords: ulnar forearm flap; vascular studies; donor site